How did the COVID-19 pandemic and digital divide impact Ciganos/Roma school pathways? - Mourão, S.; Pinheiro, S.; Maria M. M.; Caetano, P.; Magano, O. (Social Sciences, 2023)
The COVID-19 pandemic forced the Portuguese government to declare various lockdowns between 2020 and 2022. The first State of Emergency was enforced in March 2020, in which face-to-face classroom teaching was repeatedly interrupted. At that time, families were expected to provide the necessary supplies for digital learning, with some support from the government, municipalities, civil society, and local institutions. Nevertheless, many families already lived under precarious conditions before the pandemic, and so the lockdown measures increased their vulnerability, with a probable impact on student school attendance and conditions enabling academic success. Since Ciganos/Roma are part of this vulnerable population, we intend to explore how the COVID-19 pandemic impacts the school pathways of these students, namely in secondary education, where they represent a minority group. The data are derived from a variety of qualitative sources collected during research carried out in the two Metropolitan Areas in Portugal. The COVID-19 pandemic affected the youngsters’ access to classes and their motivation to attend school, and opens the discussion about how because of the government’s universal measures, by failing to consider social diversity, in particular Ciganos/Roma Ciganos/Roma families, this pandemic crisis may disproportionally affect the education of their children and youth. The findings highlight, firstly, that these impacts continue to be rendered invisible and naturalized in the public sphere and, secondly, that the measures and legislation underlying the pandemic effects continue not to include Ciganos in policymaking processes